2017
DOI: 10.3906/sag-1605-141
|View full text |Cite
|
Sign up to set email alerts
|

Decreased oxidative stress may contribute to the disease process in placenta accreta

Abstract: Background/aim: The main aim of this study was to investigate serum total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and arylesterase levels in pregnant women with placenta accreta and to compare those with age-matched healthy pregnant women. Materials and methods:A total of 27 pregnant women who had clinically and pathologically proven placenta accreta and 30 age-and BMI-matched healthy pregnant women were enrolled in this case control study. Maternal serum TOS, TAS, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…It remains unclear, by which mechanism PAS modulates VWF expression. Placental hypoxia-due to an implantation of the placenta on a uterine scar-has been discussed as one factor that stimulates increased placental invasiveness [24][25][26]. It might also play a role in PAS-induced neoangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear, by which mechanism PAS modulates VWF expression. Placental hypoxia-due to an implantation of the placenta on a uterine scar-has been discussed as one factor that stimulates increased placental invasiveness [24][25][26]. It might also play a role in PAS-induced neoangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the placenta accreta spectrum, there was a decrease in the level of oxidative stress, which is probably related to a decrease in the concentration of antio-angiogenic factor, sFlt-1. 25 Su et al, reported that aspirin which is usually used as a preeclamptic prophylaxis, has a suppressive effect on sFlt-1. 26 Therefore from these findings it can be suggested that suppression of sFlt-1 will increase placental invasion and stimulate placental angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is caused by an increased production and insufficient elimination of ROS. Although the underlying exact mechanism has not been fully discovered, oxidative stress is thought to have a significant function in the pathogenesis of many disorders, such as cardiovascular diseases, hypertension, Parkinson's disease, and Alzheimer's disease (13)(14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…diseases, such as coronary artery disease (CAD) (13)(14)(15) . It was demonstrated that lowering heart rate reduces the formation of ROS in rats (16) .…”
mentioning
confidence: 99%